Energy centered maintenance : a green maintenance system - Howell, Marvin T., 1936-; Alshakhshir, Fadi S., 1982- (The Fairmont Press, Inc., 2017)
This book provides a detailed description of how to implement Energy Centered Maintenance (ECM) at any organization. It includes a new six-step technical process with detailed instructions of each of these steps explained with clear examples. Areas covered include preventative maintenance, predictive maintenance and reliability centered maintenance. ECM uses energy consumption excesses or energy waste as the primary criterion for determining specific maintenance or repair needs. Therefore, the primary purpose of this book is to provide strategies to reduce energy use by identifying equipme.